2019
DOI: 10.1161/circresaha.118.313348
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean Diet and Cardiovascular Health

Abstract: The Mediterranean diet (MedDiet), abundant in minimally processed plant-based foods, rich in monounsaturated fat from olive oil, but lower in saturated fat, meats, and dairy products, seems an ideal nutritional model for cardiovascular health. Methodological aspects of Mediterranean intervention trials, limitations in the quality of some meta-analyses, and other issues may have raised recent controversies. It remains unclear whether such limitations are important enough as to attenuate the postulated cardiovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
438
1
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 565 publications
(449 citation statements)
references
References 168 publications
1
438
1
9
Order By: Relevance
“…Several SRMAs of RCTs consistently found that the Mediterranean diet significantly decreased CVD mortality, CHD, and stroke risk. The key features of Mediterranean diet are a low intake of meat, with very low consumption of red and processed meat; a high intake of vegetables, fruits, nuts, legumes, cereals; and moderate intake of alcohol [69], all of which food groups had differing effects in CVD prevention. For instance, our review found that high intake of nuts, whole grains, and legumes, with a moderate intake of fish (2-4 servings/week) significantly decreased CVD mortality and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…Several SRMAs of RCTs consistently found that the Mediterranean diet significantly decreased CVD mortality, CHD, and stroke risk. The key features of Mediterranean diet are a low intake of meat, with very low consumption of red and processed meat; a high intake of vegetables, fruits, nuts, legumes, cereals; and moderate intake of alcohol [69], all of which food groups had differing effects in CVD prevention. For instance, our review found that high intake of nuts, whole grains, and legumes, with a moderate intake of fish (2-4 servings/week) significantly decreased CVD mortality and CVD risk.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, critical summaries of observational studies together with RCTs yielded consistent results with respect to the health benefits of a MedDiet (Martinez-Gonzalez, Gea, & Ruiz-Canela, 2019). On the other hand, an updated Cochrane review found only a low to moderate certainty of evidence for interventions with the MedDiet in primary prevention of CVDs (Rees et al, 2019).…”
Section: What Is New?mentioning
confidence: 95%
“…Recent meta‐analyses mostly confirm the favourable associations of adhering to a MedDiet (Chen et al, ; Eleftheriou et al, ; Kojima, Avgerinou, Iliffe, & Walters, ; Rosato et al, ; Shafiei, Salari‐Moghaddam, Larijani, & Esmaillzadeh, ), although the corresponding data are predominantly based on observational studies. On the one hand, critical summaries of observational studies together with RCTs yielded consistent results with respect to the health benefits of a MedDiet (Martinez‐Gonzalez, Gea, & Ruiz‐Canela, ). On the other hand, an updated Cochrane review found only a low to moderate certainty of evidence for interventions with the MedDiet in primary prevention of CVDs (Rees et al, ).…”
Section: Introductionmentioning
confidence: 93%
“…Several systematic reviews of observational prospective studies have confirmed that greater adherence to such diet is associated with better health and greater longevity. Finally, the PREDIMED study provided important experimental proof of the cardioprotective properties of the Mediterranean diet (Martinez-Gonzalez et al 2019). Consequently, physicians should pay particular attention to their patients' dietseven though curricular training is often suboptimaland insist they preferentially adopt a plant-based regimen, enriched with fish and seafoods and with dairy products.…”
Section: Introductionmentioning
confidence: 99%